TELECONSULTATION: COVID-19 AND BEYOND - RUMEAU, Pierre; CHASSANG, Gauthier (MEDECINE LEGALE DROIT MEDICAL, 2025)
At the time of the Covid-19 pandemic, French medicine and society were receptive to the implementation of teleconsultation (TLC) as a common medical practice. In this article, we briefly review the historical evolution and maturation of the technical means related to telemedical practice, of which TLC is a part. We present the French choice to set up, since the law relating to health insurance in 2004 and the HPST law in 2009, a specific legislative and regulatory framework for telemedicine (TLM), in addition to common medical law, and we discuss the effect of this framework on medical consultation practices. After a brief presentation of the particularities of Covid-19 and the implementation of the policy response, we present the ad hoc developments in the regulation and practice of TLC, in particular with regard to the first two epidemic waves of 2020 in France. Finally, we present some questions which, although they concern TLC in the first place, seem to us to extend largely to the very conception of public health and to the societal choices associated with it.